BRIDGING THE GAP. - Castenholz, W. B. (The Accounting Review, 1927)
Abstract The article presents information on the concept of developing a relation between economics and accounting. According to the author, the precipice on the economic side is the concept of consumers' cost, whereas the considerably lower precipice on the accounting side is the present limited concept of inventoriable values. Profit has been defined as that increment of consumers' cost value which is ordinarily in excess of the conversion value created for consumers' needs by the merchant or manufacturer. It has been assumed that only those merchants and manufacturers who do create, through their operations, consumers' cost values will remain in business, because business cannot continue without profit. The theory of marginal utility finds its application and, sooner or later, produce a proper balance between the demands for economic goods and the activities that satisfy the demands. The article summarize that finished inventories, or merchandise for sale, should Include all the values created by the business process, except the profit which is the additional value created by the consumer's act of purchase.